2012
DOI: 10.4186/ej.2012.16.3.91
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Phenol Using Nb-Loaded ZnO Nanoparticles

Abstract: Niobium-loaded Zinc Oxide nanoparticles (Nb-loaded ZnO NPs) in the range of 20 and 40 nm were synthesized by Flame Spray Pyrolysis (FSP) technique. The crystalline phase, morphology and size of the nanoparticles were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and UV-vis spectroscopy. The specific surface area of the nanoparticles was measured by nitrogen adsorption (BET analysis). The unloaded ZnO and Nb-loaded ZnO NPs were found to have the clear spherical, hexagonal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…Significant progress has been made in recent years in synthesizing nanoparticles as environmental purification photocatalysts [5,6]. Many researchers reported that titanium dioxide (TiO 2 ), zinc oxide (ZnO) and tin dioxide (SnO 2 ) are the most active catalysts for the degradation of dyes, phenols and pesticides [7][8][9][10][11]. In addition, these semiconductors have been recognized as preferable materials for photocatalytic processes due to their photosensitivity, non-toxicity, low cost and high chemical stability [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been made in recent years in synthesizing nanoparticles as environmental purification photocatalysts [5,6]. Many researchers reported that titanium dioxide (TiO 2 ), zinc oxide (ZnO) and tin dioxide (SnO 2 ) are the most active catalysts for the degradation of dyes, phenols and pesticides [7][8][9][10][11]. In addition, these semiconductors have been recognized as preferable materials for photocatalytic processes due to their photosensitivity, non-toxicity, low cost and high chemical stability [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Different factors such as dopant(s), oxidants, and various surfactants have been found to improve the photocatalytic behavior of TiO 2 nanoparticles [13][14][15]. Numerous studies have been conducted to show the effects of various surfactants and transition metals (e.g., iron, vanadium, copper, niobium, and cobalt) as dopants in improving its photocatalytic activity [16][17][18][19][20][21]. Doping TiO 2 with slight amounts of transition elements causes trapping of the electrons, which results in narrowing of the band gap and lowering electron-hole recombination.…”
Section: Introductionmentioning
confidence: 99%
“…This work provides supports that the variations in the intermediates are the result from the difference in adsorption configuration on the surface of the catalyst. Wurtzite zinc oxide (ZnO) was chosen as the catalyst in this study because it could be synthesized in a manner such that the exposed surfaces could be controlled [15]. Two main sets of ZnO surfaces were considered; (i) zinc-terminated (0001) and oxygen-terminated (0001 ̅ ) polar surfaces located on top and bottom planes of the hexagonal ZnO crystal, and (ii) mixed-terminated (101 ̅ 0) non-polar surface appeared as the side planes of the crystal.…”
Section: Introductionmentioning
confidence: 99%